O Financiamento da educação básica no município de Toledo/PR (2013 a 2020) - CUNHA, AMANDA FERNANDES DA (2022)
This dissertation aims to analyze the relationship between the public fund and the financing of basic education in the city of Toledo/PR. The study was developed from a bibliographical and documental approach with collection and analysis of data made available on the Transparency Portal of that municipality, being organized into two chapters. Understanding the need to infer about themes that are correlated and that affect the object of study, in the first chapter we seek to assimilate aspects of the budget and educational funds (FUNDEF, FUNDEB and FUNDEB Permanente). To achieve our purpose, we approached other themes that helped us to understand our object of study, namely: Brazilian federalism and constitutional transfers, the capital crisis and social policies in Brazil, international organizations, State reform and financialization, public debt. In the second chapter, the objective of this study was to appropriate the object of this study, being the financing of public education in the city of Toledo/PR, with a time frame from 2013 to 2020. For this purpose, data related to the movements of income and expenses were analyzed of the municipality. We also carried out the characterization of the Municipal Public Education Network, presenting the numbers related to enrollment, numbers of teachers and employees. Finally, we examine the data referring to revenues and expenses with maintenance and development of education (MDE), with FUNDEB and with the Education Function. From the analysis of the data and its correlation with the bibliographic study, it was possible to verify that, despite the municipality having a surplus budget, investment in the area of education is limited to complying with what is provided for by law, even having conditions to expand investment in this area.